Improving oral health of children in four Balkan countries: A qualitative study among health professionals - Karamehmedovic, Enes; Petersen, Poul Erik; Agdal, Maren L.; Virtanen, Jorma I. (Frontiers in Oral Health, 2023)
Data from the World Health Organization show that the oral health situation for children in the Balkan region of Europe is poor. This study aims to identify obstacles that prevent the implementation of an effective oral health program for children in the Balkan area. The study investigates the challenges that people encounter in increasing awareness, attending to dental care, and complying with examinations. Methods: This qualitative study targeted experts in preventive dentistry and oral health promotion in four countries in the Balkan region. Purposive sampling was used to recruit the participants. Data were collected in 2021 using individual in-depth interviews with participants from Albania, Bosnia and Herzegovina, Croatia, and Serbia. The study applied the thematic analysis method. Results: The experts reported four main challenges that hindered the implementation of a prevention program and regular patient attendance: (1) lack of knowledge, (2) the exclusion of oral health from overall health, 3) organization of services, and (4) skepticism of fluoride. The participants identified knowledge gaps among the general population, dental staff, and other health professionals regarding the prevention of oral diseases. Conclusion: The findings of this study may be used to promote and improve oral health among children in the identified areas and to benefit people in the region and elsewhere. This study sheds light on the existing barriers in a region where people lack information.